Insight into the surfactin production of Bacillus velezensis B006 through metabolomics analysis. (1st December 2018) - Wang, Junqiang; Guo, Rongjun; Wang, Wenchao; Ma, Guizhen; Li, Shidong
Abstract: Bacillus velezensis B006 is a biocontrol agent which functions through effective colonization and surfactin production. To reveal the surfactin-producing mechanism, gas chromatography–mass spectrometry based untargeted metabolomics was performed to compare the metabolite profiles of strain B006 grown in industrial media M3 and M4. Based on the statistical and pathway topology analyses, a total of 31 metabolites with a fold change of less than − 1.0 were screened as the significantly altered metabolites, which distributed in 15 metabolic pathways. Fourteen amino acids involving in the metabolisms of alanine/aspartate/glutamate, glycine/serine/threonine, arginine/proline, glutathione/cysteine/methionine and valine/leucine/isoleucine as well as succinic acid in TCA cycle were identified to be the hub metabolites. Aminoacyl-tRNA biosynthesis, glycerolipid metabolism, and pantothenate/CoA biosynthesis also contributed to surfactin production. To the best of our knowledge, this study is the first to investigate the metabolic pathways of B. velezensis on surfactin production, and will benefit the optimization of commercial fermentation for higher surfactin yield.